Yellow fever epizootics in non-human primates, São Paulo state, Brazil, 2008-2009 - Moreno, Eduardo Stramandinoli; Spinola, Roberta; Tengan, Cilea Hatsumi; Brasil, Roosecelis Araujo; Siciliano, Melissa Mascheratti; Coimbra, Terezinha Lisieux Moraes; Silveira, Vivian Regina; Rocco, Iray Maria; Bisordi, Ivani; Souza, Renato Pereira de; Petrella, Selma; Pereira, Luiz Eloy; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
Since 2000, the expansion of Sylvatic Yellow Fever (YF) has been observed in the southeast of Brazil, being detected in areas considered silent for decades. Epizootics in non-human primates (NHPs) are considered sentinel events for the detection of human cases. It is important to report epizootic events that could have impact on the conservation status of susceptible species. We describe the epizootics in NHPs, notified in state of São Paulo, Brazil, between September 2008 to August 2009. Ninety-one epizootic events, involving 147 animals, were reported in 36 counties. Samples were obtained from 65 animals (44.2%). Most of the epizootics (46.6%) were reported between March and April, the same period during which human cases of YF occurred in the state. Biological samples were collected from animals found dead and were sent to Instituto Adolfo Lutz, in São Paulo. Two samples, collected in two counties without an indication for YF vaccination, were positive for the virus. Another 48 animals were associated with YF by clinical-epidemiological linkage with laboratory confirmed cases. Because the disease in human and NHPs occurred in the same period, the detection of the virus in NHPs did not work as sentinel, but aided in the delineation of new areas of risk.